Analisis Pengaruh Pembayaran Zakat Mal Terhadap Pengurangan Kewajiban Pajak di Indonesia - Helma Maulana Dzulfikar; Mabruri Andatu; Reza Apriza; Yek Nizar Ali; Balqis Farid; Fathiya ZN Azizah (IQTISHOD: Jurnal Pemikiran dan Hukum Ekonomi Syariah, 2025)
This research is motivated by the debate regarding the recognition of zakat as a deduction from income tax for Muslim taxpayers, as regulated in Law No. 23 of 2011 and related tax regulations. The purpose of this research is to analyze the extent to which the payment of zakat mal can influence income tax obligations, as well as to review the implementation of this policy in practice. The method used is a quantitative approach with secondary data analysis from taxpayer data and official zakat collection institutions. The results show that there is a significant negative relationship between the payment of zakat mal and the amount of tax obligation that must be paid, especially if the zakat is paid through officially registered zakat institutions. The conclusion of this research shows that zakat mal can serve as a reduction in income tax, although its effectiveness is greatly influenced by administrative compliance and taxpayers understanding of the applicable regulations. Therefore, it is recommended that the government enhance the socialization and integration of the zakat and taxation systems to optimize yhe benefits of this policy.